Can COVID-19 impact the natural history of paracoccidioidomycosis? Insights from an atypical chronic form of the mycosis - Souza, César Augusto Tomaz de; Ponce, Cesar Cilento; Klautau, Gisele Burlamaqui; Marques, Nathan Costa; Queiroz, Wladimir; Patzina, Rosely Antunes; Benard, Gil; Lindoso, José Angelo Lauletta (Revista do Instituto de Medicina Tropical de São Paulo, 2023)
Paracoccidioidomycosis (PCM) is a systemic fungal infection caused by Paracoccidioides spp. It can occur as an acute/subacute form (A/SAF), a chronic form (CF) and rarely as a mixed form combining the features of the two aforementioned forms in an immunocompromised patient. Here, we report a 56-year-old male patient with CF-PCM who presented with atypical manifestations, including the development of an initial esophageal ulcer, followed by central nervous system (CNS) lesions and cervical and abdominal lymphatic involvement concomitant with severe SARS-CoV-2 infection. He was HIV-negative and had no other signs of previous immunodeficiency. Biopsy of the ulcer confirmed its mycotic etiology. He was hospitalized for treatment of COVID-19 and required supplemental oxygen in the intensive unit. The patient recovered without the need for invasive ventilatory support. Investigation of the extent of disease during hospitalization revealed severe lymphatic involvement typical of A/SAF, although the patient`s long history of high-risk exposure to PCM, and lung involvement typical of the CF. Esophageal involvement is rare in non-immunosuppressed PCM patients. CNS involvement is also rare. We suggest that the immunological imbalance caused by the severe COVID-19 infection may have contributed to the patient developing atypical severe CF, which resembles the PCM mixed form of immunosuppressed patients. Severe COVID-19 infection is known to impair the cell-mediated immune response, including the antiviral response, through T-lymphopenia, decreased NK cell counts and T-cell exhaustion. We hypothesize that these alterations would also impair antifungal defenses. Our case highlights the potential influence of COVID-19 on the course of PCM. Fortunately, the patient was timely treated for both diseases, evolving favorably.